(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The article analyzes the processes and methods of cooling large and small power transformers used in power supply systems. The modern state of transformers and the issues of energy resource saving in them are considered. Also, systems that protect against explosions in voltage and load modes, short circuits and fires resulting from oil leakage in the housing are studied. A functional scheme of an automated cooling system has been developed by monitoring the technical condition of the transformer. An automated cooling system and device that protects transformers from fire and explosion have been designed and substantiated by a feasibility study. Rules for using an automated cooling system and commissioning the device have been developed. The system for remote monitoring and control of all technological and operational indicators, as well as their schemes, have been improved.